Plant Pollen Grains: A Move Towards Green Drug and Vaccine Delivery Systems - Iravani, Siavash; Varma, Rajender S (Nano-micro letters, 2021)
Pollen grains and plant spores have emerged as innovative biomaterials for various applications such as drug/vaccine delivery, catalyst support, and the removal of heavy metals. The natural microcapsules comprising spore shells and pollen grain are designed for protecting the genetic materials of plants from exterior impairments. Two layers make up the shell, the outer layer (exine) that comprised largely of sporopollenin, and the inner layer (intine) that built chiefly of cellulose. These microcapsule shells, namely hollow sporopollenin exine capsules have some salient features such as homogeneity in size, non-toxic nature, resilience to both alkalis and acids, and the potential to withstand at elevated temperatures; they have displayed promising potential for the microencapsulation and the controlled drug delivery/release. The important attribute of mucoadhesion to intestinal tissues can prolong the interaction of sporopollenin with the intestinal mucosa directing to an augmented effectiveness of nutraceutical or drug delivery. Here, current trends and prospects related to the application of plant pollen grains for the delivery of vaccines and drugs and vaccine are discussed.
Keywords: Sporopollenin; Drug delivery; Microcapsule shells; Pollens; Vaccine delivery; Plant pollen grains